Citizenship and disadvantaged groups in Chile - Marshall, Pablo (Lexington Books, 2019)
Citizenship and Disadvantaged Groups in Chile seeks to overcome an existing void in the literature of Latin American studies addressing the impact of Chile's post dictatorial legal framework on its historically and structurally disadvantaged groups, concentrating on the various issues and challenges that affect them. Within its eleven chapters it explores the changing social and legal status of LGBTI people, the political disenfranchisement and the social exclusion that affects imprisoned individuals, the harshness of policing on poor and marginalized communities, the deprivation of Indigenous peoples of meaningful rights, the vulnerability that affects workers as a consequence of the existing model of labor relations, the disenfranchisement that affects migrants seeking economic opportunities, the denial of citizenship to women involved in the prohibition of abortion, the unsatisfactory regulation of sex work, the prevalence of domestic violence, and the absence of adequate means for disadvantaged groups to institutionalize their political representation. This book offers a distinctive contribution, focusing on a specific country in the Global South that is presently undergoing a process of economic consolidation while facing many of the problems of traditional and unequal Latin American societies.